Rationale for a Stronger Disposition of Chardonnay Wines for Stuck and Sluggish Fermentation - Sommer, S.; Wegmann-Herr, P.; Wacker, M.; Fischer, U. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to identify and evaluate factors that contribute to fermentation problems in Chardonnay, since this variety is reported to have frequent problems. Analytical methods included gas chromatography mass spectrometry, as well as atomic absorption spectroscopy and FT-MIR spectroscopy. Chardonnay, Pinot blanc, Pinot noir and Pinot noir précoce were screened to relate observations to specific varietal properties. The results show a significant distinction in the amino acid profile of Chardonnay, which can be correlated with sluggish fermentation. A comparison between the fatty acid profile of Chardonnay and Pinot blanc reveals that Chardonnay contains more toxic compounds, which inhibit yeast metabolism. Mineral supply and potential metal toxicity were also analysed. The concentrations of iron, copper, magnesium, zinc and manganese show significant variations among the grape varieties. In conclusion, the possible causes for stuck fermentation in Chardonnay could be more related more to variety than to oenological decisions.